The Post-Soviet Space and Turkey: The Results of 30 Years - V. A. Avatkov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
The article scrutinizes the main results of the 30-year independent existence of the former Soviet republics under the conditions of modern political realities and the formation of a polycentric system of international relations, where regional states such as Turkey begin to exert an increasing influence on the ongoing processes. Based on the results of the analysis, the author comes to the conclusion that since the collapse of the Soviet Union, two trends have developed in the post-Soviet space: integration and disintegration. e main task of the Republic of Turkey in the post-Soviet region is to set the pro-Turkish model of integration of key Turkic states and to create the so-called “Turkic world” – a new subsystem of international relations under its auspices. In order to implement these plans, Ankara pursues three main goals in the post-Soviet space: to replace the “Turkic” with the “Turkish”; secondly, to bring loyal elites to power in the partner countries; and to concentrate the movement of resources within the framework of the “hub” ideology. Meanwhile, during its interaction with the former USSR countries Turkey has passed or is still passing through several stages: the “era of hope”, the “step-by-step era” and the “era of Turkish-centric integration”, which continues up to the present time and is expressed in exerting a significant influence on the Turkic actors.